Internet connectivity disruption in SS (South Sudan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in South Sudan. Data sourced from IODA.
Network Disruption Incident ID: SS-2026-0007. Severity: critical. Confidence: 67%